2020
DOI: 10.18231/2394-6792.2018.0073
|View full text |Cite
|
Sign up to set email alerts
|

Study of fine needle aspiration cytology of palpable head and neck lesions in tertiary care centre

Abstract: Introduction: Fine Needle Aspiration Cytology (FNAC) of neck masses is a quick, easy, safe and cheap technique and has been a well accepted procedure in diagnosing various swellings. In head and neck regions FNAC is widely used such as in the lymph nodes, thyroid, salivary glands and other neoplasms. Aims and Objectives: 1.To evaluates the role of FNAC and its utility in diagnosis of palpable head and neck masses; 2. To study the spectrum of head and neck lesions in rural population; 3. To study diagnostic acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 7 publications
1
4
1
Order By: Relevance
“…Other studies also observed reactive lymphadenitis as the most common diagnosis similar to this study. 10,13,17,20,21 In the present study female predominance was seen in lymph nodes in contrast to the other studies where there was male predominance. 9,11 In contrast to our study where TB lymphadenitis was the second most common cause (14%), few other studies showed TB lymphadenitis as the most frequent cause of lymph node swelling.…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations
“…Other studies also observed reactive lymphadenitis as the most common diagnosis similar to this study. 10,13,17,20,21 In the present study female predominance was seen in lymph nodes in contrast to the other studies where there was male predominance. 9,11 In contrast to our study where TB lymphadenitis was the second most common cause (14%), few other studies showed TB lymphadenitis as the most frequent cause of lymph node swelling.…”
Section: Discussioncontrasting
confidence: 81%
“…3,[9][10][11][12] In the present study, the overall head, and neck swellings were more commonly encountered in females with male to female ratio being 1:2.2 which is similar to other studies. 9,[13][14][15] The peak incidence of head and neck lesions in the majority of the studies was in the second decade, unlike the present study where the lesions were seen in the fourth decade (18.4%). 9,13,16,17 Similar to the studies done by Khetrapal et al, 9 nonneoplastic lesions were the dominant cause for head and neck swelling in the present study.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The study of Shaan Khetrapal et al [15] noted that the largest number of cases from lymph node lesions 64.1% and the least number of cases were from oral cavity 1.03% which is comparable to the present study. [16] found 67.3% and the study of Dr. Kusum Borsaikia [23] found 62.50% and study of Apoorva KP et al [24] found 64.5%. In the present study, Papillary carcinoma was highest 10% in a malignant lesion which is similar to the study of Rashmi Rekha Goswami et al [16] noted 5.4% and the study of Chauhan Savitri et al [25] noted 3.1%.…”
Section: Discussionmentioning
confidence: 99%